Oxidative Stress-Mediated Atherosclerosis: Mechanisms and Therapies - Yang, Xinyu; Li, Yang; Li, Yanda; Ren, Xiaomeng; Zhang, Xiaoyu; Hu, Dan; Gao, Yonghong; Xing, Yanwei; Shang, Hongcai (Frontiers in Physiology, 2017)
Atherogenesis, the formation of atherosclerotic plaques, is a complex process that involves several mechanisms, including endothelial dysfunction, neovascularization, vascular proliferation, apoptosis, matrix degradation, inflammation, and thrombosis. The pathogenesis and progression of atherosclerosis are explained differently by different scholars. One of the most common theories is the disruption of normal homeostatic mechanisms, which triggers an oxidative stress. Oxidative stress is widely defined as the redox state achieved when an imbalance exists between antioxidant capacity and reactive species including reactive oxygen (ROS), nitrogen (RNS) and halogen species, non-radical as well as free radical species. This occurrence results in cell injury due to direct oxidation of cellular protein, lipid, and DNA or via cell death signaling pathways responsible for accelerating atherogenesis. This paper discusses inflammation, mitochondria, autophagy, apoptosis, and epigenetics as they induce oxidative stress in atherosclerosis, as well as various treatments for antioxidative stress that may prevent atherosclerosis.